Pengaruh job insecurity terhadap employee performance melalui procedural justice pada karyawan PT. Kerta Rajasa Raya - Erlynda Sabirina; Khoirur Rozaq (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to examine and analyze the effect of job insecurity on employee performance through procedural justice for employees of PT. X. The approach used in this research is quantitative. The sampling technique uses a saturated sample with a total of 46 employees. The data in this study were analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) with the help of smartPLS 4.0 software. The results showed that job insecurity had a significant negative effect on employee performance, job insecurity had a significant negative effect on procedural justice, procedural justice had a significant positive effect on employee performance, the role of procedural justice mediated a negative effect between job insecurity on employee performance. The implications of these findings that can be applied to PT X is that companies must further improve and improve procedural justice and after that only by increasing job insecurity by improving and increasing employee performance in the company